Cloning, Expression, and Purification of Recombinant Protein from a Single Synthetic Multivalent Construct of Mycobacterium Tuberculosis - Fang, Chee Mun; Zainuddin, Zainul F.; Musa, Mustaffa; Thong, Kwai Lin (Elsevier, 2006)
Tuberculosis remains a major infectious disease with over 8 million new cases and 2 million deaths annually. Therefore, a vaccine more potent than BCG is desperately needed. In this regard, an approximately 800 bp DNA encoding a mycobacterial synthetic gene designated as VacIII (containing ubiquitin gene UbGR and four immunogenic mycobacterial epitopes or genes of ESAT-6, Phos1, Hsp 16.3, and Mtb8.4) was sub-cloned into a bacterial expression vector of pRSET-B resulting in a 6x His-VaeIII fusion gene construction. This recombinant clone was over expressed in Escherichia coli BL-21 (DE-3). The expressed fusion protein was found almost entirely in the insoluble form (inclusion bodies) in cell lysate. The inclusion bodies were solubilized with 8 M urea and the recombinant protein was purified by Ni-NTA column and dialyzed by urea gradient dialysis. This method produced a relatively high yield of recombinant VacIII protein and the cloned VacIII gene offers the potential development of other vaccine formats such as DNA vaccine and recombinant vaccine. (c) 2006 Elsevier Inc. All rights reserved.